Nitrosonium nitrate (NO+NO3) structure solution using in situ single-crystal X-ray diffraction in a diamond anvil cell. (March 2021) - Laniel, Dominique; Winkler, Bjoern; Koemets, Egor; Fedotenko, Timofey; Chariton, Stella; Milman, Victor; Glazyrin, Konstantin; Prakapenka, Vitali; Dubrovinskyc, Leonid; Dubrovinskaiaa, Natalia
No abstract available